The level of endogenous testosterone and its correlation with lipid profile in men older than 40 years with acute myocardial infarction - Barać, Branko; Stanković, Sanja; Ašanin, Milika; Vasiljević-Pokrajčić, Zorana; Vujović, Svetlana (Vojnosanitetski pregled, 2021)
Background/Aim. The influence of lipid profile on acute myocardial infarct (AMI) is well known. On the other hand, the role of testosterone (T), as one of the possible predictive factors of AMI in men and its influence on lipid profile in men is still controversial. The aim of the study was to determine levels of T in AMI and six months after AMI in the same group of patients, and to compare with T levels in healthy men. Also we correlated T levels with lipid profile in patients with AMI and 6 months after AMI. Methods. The study was designed as prospective study. Patients were divided into III groups: Group I included 35 men, aged 55 ± 3 years, with AMI. Group II included the same 35 patients, analyzed 6 months after AMI. The group III consisted of 20 healthy men aged 57 ± 2.12 years (control group). Blood samples of the group I (AMI) were taken in the first 12 hours from the AMI beginning and also 6 months after AMI (group II). Following analyses were performed: levels of total cholesterol, triglycerides, low density lipoprotein (LDL) cholesterol, high density lipoprotein (HDL) cholesterol, lipoprotein(a) [Lp(a)], apolipoprotein A1 (Apo A1), apolipoprotein B (Apo B) and T. Results. Levels of T in patients with AMI (16.86 ± 7.18 nmol/L) as well as 6 months after AMI (18.12 ± 7.96 nmol/L) were statistically significantly lower than those in healthy persons of the same age (27.11 ± 10.48 nmol/L) (p < 0.001). In the group I, statistically significant, positive correlation was found between levels of T and HDL cholesterol (r = 0.403, p < 0.05), and levels of T and Apo A1 (r = 0.747, p < 0.01). In the group II, statistically significant, positive correlation was also found between levels of T and HDL cholesterol (r = 0.388, p < 0.05) and T and Apo A1(r = 0.354, p < 0.05). Conclusion. This study showed that men, over 40 years of age, with AMI had statistically significantly lower concentrations of endogenous T compared to healthy male population of the same age. Levels of T in the same patients after 6 months from AMI maintained statistically significantly lower values in comparison to those in healthy men.